The Future of Electric Power in the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Electric power is essential for the lives and livelihoods of all Americans, and the need for electricity that is safe, clean, affordable, and reliable will only grow in the decades to come. At the request of Congress and the Department of Energy, the National Academies convened a committee of experts to undertake a comprehensive evaluation of the U.S. grid and how it might evolve in response to advances in new energy technologies, changes in demand, and future innovation. The Future of Electric Power in the United States presents an extensive set of policy and funding recommendations aimed at modernizing the U.S. electric system. The report addresses technology development, operations, grid architectures, and business practices, as well as ways to make the electricity system safe, secure, sustainable, equitable, and resilient.
Keywords: Energy and Energy Conservation

Global Change Research Needs and Opportunities for 2022-2031 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The US Global Change Research Program (USGCRP) is a collection of 13 Federal entities charged by law to assist the United States and the world to understand, assess, predict, and respond to human-induced and natural processes of global change. Global Change Research Needs and Opportunities for 2022-2031 advises the USGCRP on how best to meet its mandate in light of climate change impacts happening today and projected into the future. This report identifies critical climate change risks, research needed to support decision-making relevant to managing these risks, and opportunities for the USGCRP's participating agencies and other partners to advance these research priorities over the next decade.
Keywords: Behavioral and Social Sciences; Environment and Environmental Studies

Accelerating Decarbonization of the U.S. Energy System - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The world is transforming its energy system from one dominated by fossil fuel combustion to one with net-zero emissions of carbon dioxide (CO2), the primary anthropogenic greenhouse gas. This energy transition is critical to mitigating climate change, protecting human health, and revitalizing the U.S. economy. To help policymakers, businesses, communities, and the public better understand what a net-zero transition would mean for the United States, the National Academies of Sciences, Engineering and Medicine convened a committee of experts to investigate how the U.S. could best decarbonize its transportation, electricity, buildings, and industrial sectors. This report, Accelerating Decarbonization of the United States Energy System, identifies key technological and socio-economic goals that must be achieved to put the United States on the path to reach net-zero carbon emissions by 2050. The report presents a policy blueprint outlining critical near-term actions for the first decade (2021-2030) of this 30-year effort, including ways to support communities that will be most impacted by the transition.
Keywords: Environment and Environmental Studies; Energy and Energy Conservation

Cultivating Interest and Competencies in Computing: Authentic Experiences and Design Factors - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Computing in some form touches nearly every aspect of day to day life and is reflected in the ubiquitous use of cell phones, the expansion of automation into many industries, and the vast amounts of data that are routinely gathered about people's health, education, and buying habits. Computing is now a part of nearly every occupation, not only those in the technology industry. Given the ubiquity of computing in both personal and professional life, there are increasing calls for all learners to participate in learning experiences related to computing including more formal experiences offered in schools, opportunities in youth development programs and after-school clubs, or self-initiated hands-on experiences at home. At the same time, the lack of diversity in the computing workforce and in programs that engage learners in computing is well-documented. It is important to consider how to increase access and design experiences for a wide range of learners. Authentic experiences in STEM - that is, experiences that reflect professional practice and also connect learners to real-world problems that they care about - are one possible approach for reaching a broader range of learners. These experiences can be designed for learners of all ages and implemented in a wide range of settings. However, the role they play in developing youths' interests, capacities, and productive learning identities for computing is unclear. There is a need to better understand the role of authentic STEM experiences in supporting the development of interests, competencies, and skills related to computing. Cultivating Interest and Competencies in Computing examines the evidence on learning and teaching using authentic, open-ended pedagogical approaches and learning experiences for children and youth in grades K-12 in both formal and informal settings. This report gives particular attention to approaches and experiences that promote the success of children and youth from groups that are typically underrepresented in computing fields. Cultivating Interest and Competencies in Computing provides guidance for educators and facilitators, program designers, and other key stakeholders on how to support learners as they engage in authentic learning experiences.
Keywords: Education; Computers and Information Technology

Reflecting Sunlight: Recommendations for Solar Geoengineering Research and Research Governance - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Climate change is creating impacts that are widespread and severe for individuals, communities, economies, and ecosystems around the world. While efforts to reduce emissions and adapt to climate impacts are the first line of defense, researchers are exploring other options to reduce warming. Solar geoengineering strategies are designed to cool Earth either by adding small reflective particles to the upper atmosphere, by increasing reflective cloud cover in the lower atmosphere, or by thinning high-altitude clouds that can absorb heat. While such strategies have the potential to reduce global temperatures, they could also introduce an array of unknown or negative consequences. This report concludes that a strategic investment in research is needed to enhance policymakers' understanding of climate response options. The United States should develop a transdisciplinary research program, in collaboration with other nations, to advance understanding of solar geoengineering's technical feasibility and effectiveness, possible impacts on society and the environment, and social dimensions such as public perceptions, political and economic dynamics, and ethical and equity considerations. The program should operate under robust research governance that includes such elements as a research code of conduct, a public registry for research, permitting systems for outdoor experiments, guidance on intellectual property, and inclusive public and stakeholder engagement processes.
Keywords: Earth Sciences; Environment and Environmental Studies; Engineering and Technology

Plasma Science: Enabling Technology, Sustainability, Security, and Exploration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Plasma Science and Engineering transforms fundamental scientific research into powerful societal applications, from materials processing and healthcare to forecasting space weather. Plasma Science: Enabling Technology, Sustainability, Security and Exploration discusses the importance of plasma research, identifies important grand challenges for the next decade, and makes recommendations on funding and workforce. This publication will help federal agencies, policymakers, and academic leadership understand the importance of plasma research and make informed decisions about plasma science funding, workforce, and research directions.
Keywords: Math, Chemistry, and Physics; Space and Aeronautics

Progress Toward Restoring the Everglades: The Eighth Biennial Review - 2020 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
During the past century, the Everglades, one of the world's treasured ecosystems, has been dramatically altered by drainage and water management infrastructure to improve flood management, urban water supply, and agricultural production. The remnants of the original Everglades now compete for water with urban and agricultural interests and are impaired by contaminated runoff from these two sectors. The Comprehensive Everglades Restoration Plan (CERP), a joint effort launched by the state and the federal government in 2000, seeks to reverse the decline of the ecosystem. The multibillion-dollar project was originally envisioned as a 30- to 40-year effort to achieve ecological restoration by reestablishing the natural hydrologic characteristics of the Everglades, where feasible, and to create a water system that serves the needs of both the natural and the human systems of South Florida. In establishing the CERP, Congress also requested that an independent scientific review be conducted on progress toward restoration with biennial reports. The National Academies' Committee on Independent Scientific Review of Everglades Restoration Progress has provided biennial reviews of restoration progress and advice on scientific and engineering issues that may impact progress since 2004. This eighth study of the series describes substantive accomplishments over the past 2 years and reviews developments in research, monitoring, and assessment that inform restoration decision making. Progress Toward Restoring the Everglades: The Eighth Biennial Review - 2020 also reviews the recently developed Combined Operational Plan, which is a prerequisite for CERP progress in the central Everglades, and examines issues facing the northern and southern estuaries, including priorities for science to support restoration decision making.
Keywords: Environment and Environmental Studies; Earth Sciences

The Challenge of Feeding the World Sustainably: Summary of the US-UK Scientific Forum on Sustainable Agriculture - National Academy of Sciences (The National Academies Press, 2021)
The need for sustainable agriculture is becoming ever more significant. The world's population is still increasing, requiring more from our agricultural systems. Malnutrition and diet-related illnesses are present in nearly all societies. At the same time, agriculture plays a significant role in some of the biggest environmental challenges that humanity is facing, including the climate crisis, biodiversity loss, deforestation, and the pollution of our soil, water, and air. The need to balance the growing demand for nutritious food with these environmental threats is a complex issue, and ensuring sustainable food systems will require a collaborative effort from many different communities. These issues were addressed during the US-UK Scientific Forum on Sustainable Agriculture held in Washington, DC, on March 5-6, 2020. Organized by the National Academy of Sciences and the United Kingdom's Royal Society, the forum brought together leading scientists, researchers, policy makers, and practitioners in agricultural sciences, food policy, biodiversity, and environmental science (among other specialties). The forum provided an opportunity for members of these research communities to build multidisciplinary and international collaborations that can inform solutions to a broad set of problems. This publication summarizes the presentations of the forum.
Keywords: Environment and Environmental Studies; Agriculture

The Role of Transit, Shared Modes, and Public Policy in the New Mobility Landscape - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
If combined with public transit and increased in scale, shared modes of transportation, such as ride-hailing, scooter sharing and bike sharing, can enhance mobility, equity, and sustainability in metropolitan areas. Cities, transit agencies, and shared mobility providers should collaborate in goal-setting, experimentation, testing, and implementation. These are among the findings in TRB Special Report 337: The Role of Transit, Shared Modes, and Public Policy in the New Mobility Landscape, from TRB of the National Academies of Sciences, Engineering, and Medicine. The report's authors recommend deliberate and strategic measures in order to realize the full and potentially transformative benefits of shared services. These measures include providing travelers with real- or near real-time information on combinations of available price and service offerings, smartphone applications that simplify the process of arranging and paying for the use of multiple transportation modes for a single trip, and more public sector coordination of services across modes and jurisdictions.
Keywords: Transportation and Infrastructure